2010
DOI: 10.1088/0965-0393/18/4/045005
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanics prediction of the effective elastic moduli of graphene sheet-reinforced polymer nanocomposites

Abstract: We investigate the stiffening effect of graphene sheets dispersed in polymer nanocomposites using the Mori-Tanaka micromechanics method. The effective elastic moduli of graphene sheet-reinforced composites are first predicted by assuming that all the graphene sheets are either aligned or randomly oriented in the polymer matrix while maintaining their platelet-like shape. It is shown that a very low content of graphene sheets can considerably enhance the effective stiffness of the composite. The superiority of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(108 citation statements)
references
References 34 publications
5
103
0
Order By: Relevance
“…In most of the reported literature, the mechanical properties increased up to 1 wt% of graphene and decreased afterwards which can be attributed to agglomeration of graphene and generation of cracks around the graphene agglomerates [90] [139]. The MTM showed increasing values of Young's modulus with increasing weight fraction of graphene [140]. However, in atomistic simulation, the results showed that Young's modulus increases up to certain weight fraction of graphene and then starts decreasing depending on the parameters [43].…”
Section: Weight Fractionmentioning
confidence: 99%
“…In most of the reported literature, the mechanical properties increased up to 1 wt% of graphene and decreased afterwards which can be attributed to agglomeration of graphene and generation of cracks around the graphene agglomerates [90] [139]. The MTM showed increasing values of Young's modulus with increasing weight fraction of graphene [140]. However, in atomistic simulation, the results showed that Young's modulus increases up to certain weight fraction of graphene and then starts decreasing depending on the parameters [43].…”
Section: Weight Fractionmentioning
confidence: 99%
“…(23)- (27), the coefficients of strain concentration tensor Ay have been derived in Eqs. (15)- (20).…”
Section: Efîective Elastic Properties Due To Agglomeration Effect Witmentioning
confidence: 99%
“…Moreover, from the experimental works, it is also clear that complete deagglomeration may not be practically feasible [1][2][3][4][5][6][7][8][9][10][11]. The stiffening effect of graphene sheets dispersed in polymer nanocomposites using the Mori-Tanaka micromechanics method has been investigated [20]. The effective elastic moduli including the agglomeration effects of graphene sheet-reinforced composites are predicted for both aligneci and random orientations.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene-based polymer composites (Ji et al (2010)) are widely studied using micro-mechanics tools like the scheme by Mori and Tanaka 3 (1973). However, to derive the effective properties of such composite materials, the Eshelby's tensor for the Graphene sheet accounting for its real geometrical morphology is less discussed and remain a challenging task.…”
Section: Introductionmentioning
confidence: 99%